Dominant gastrointestinal strongylatosis in sheep in the context of the altitudinal zonation in Dagestan - M. M. Zubairova; A. M. Atayev; N. T. Karsakov; A. N. Khasaev (Российский паразитологический журнал, 2024)
The purpose of the research is to study the epizootology of the dominant gastrointestinal strongylatosis in sheep in different natural zones of Dagestan.Materials and methods. In 2005–2021, 180 forestomachs of the thin and thick sections of the digestive tract and 600 fecal samples from sheep at the altitude (above 2000 m above sea level) were studied based on dissection results. The study was performed by season among young animals aged up to 1 year, from 1 to 2 years and 3 years and older. The study used methods of complete helminthological dissection per K. I. Skryabin, larvae cultivation in a thermostat at 27 оC, and flotation with a saturated ammonium nitrate solution by Kotelnikov-Khrenov and Berman-Orlov.Results and discussion. Helminth infections are recorded among sheep annually on lowland, moist, steppe pastures of the plains and foothills in various combinations of multiple infections with the prevalence of 11.2–18.7% and the infection intensity of 18.5–186.4 sp./animal. In the mountain zone at altitudes above 2000 m above sea level, the quantitative and qualitative indicators of helminthosis pathogens were sharply limited. On these lands, dicrocoeliosis, monieziosis, larval echinococcosis, chabertiosis, haemonchosis, and nematodirosis were recorded in sheep with the prevalence of 3.2–10.4% and the infection intensity of 2.4–6.3 sp./animal. Gastrointestinal Strongylata dominate in sheep on all types of pastures in the lowland, foothill, and mountain zones: Chabertia ovina, Bunostomum trigоnocephalum, Trichostrongylus axei, T. capricola, T. colubriformis, T. vitrinus, Haemonchus contortus, Nematodirus filicollis, N. helvetianus, N. oiratianus, and N. spathiger.